Factor Xa Inhibitor Attenuates Leukocyte Adhesion and Thrombus Formation in an Experimental Mouse Model of the Metabolic Syndrome. Issue 5 (12th September 2013) - Iba, Toshiaki; Aihara, Koichiro; Watanabe, Shin; Yanagawa, Youichi; Yamada, Atushi; Koichiro, Niwa; Ohsaka, Akimichi
Summary: Aims: In a model of acute inflammation, Factor Xa inhibitors have been reported not only to suppress the coagulation system but also to exert anti‐inflammatory effects. However, this has not been experimentally demonstrated in a model of chronic inflammation. Recent studies demonstrated that vascular inflammation in the metabolic syndrome plays major roles in the development of thrombotic diseases. Therefore, we examined the anti‐inflammatory effects of fondaparinux, a Factor Xa inhibitor, in a mouse model of the metabolic syndrome, looking at both leukocyte adhesion on the vascular endothelium and thrombus formation. Methods: Following clamping of the mesenteric vein for 20 min in the KK‐A y mouse, mice were administered by subcutaneous injection either low‐dose or high‐dose fondaparinux or placebo (n = 10 in each group. Microscopic observation of the intestinal microcirculation was carried out. In another series, blood samples were taken and measured for blood cell counts and organ damage markers (n = 6 in each). Results: Both leukocyte adherence and thrombus formation were inhibited by treatment with fondaparinux. Red blood cell and white blood cell counts were maintained better in high‐dose group. Levels of alanine aminotransferase (ALT) were significantly reduced in both low‐dose and high‐dose groups ( P < 0.05 and 0.01, compared with control, respectively). Conclusions: Factor Xa inhibitor attenuates leukocyte adhesion and leukocyte‐platelet conjugate formation in a mouse model of the metabolic syndrome. These effects appeared to be related to both inhibition of thrombus formation and reduction in markers of organ damage.